Allicin modulates the intestinal microbiota to attenuate blood glucose and systemic inflammation in type 2 diabetic rats - Li, LinZehao; Yan, Yan; Wang, Xiaolei; Hou, Yanli; Ding, Lina; Wang, Zhibin; Song, Qinghe; Ding, Wenyu; Zhang, Xiandang (Frontiers in Microbiomes, 2023)
Allicin is a wide spectrum prebiotic for human health, but whether it can attenuate blood glucose in diabetes patients is rarely reported. In this study, we built a rat model and investigated the effect of allicin on T2DM. We found that allicin could effectively attenuate blood glucose levels and reduce lipid and weight accumulation and systemic inflammation in T2DM rats. Intestinal microbiome analysis showed that allicin gavage significantly regulated the structure and main components of the intestinal microbiota in T2DM rats. Allicin increased the abundance of probiotic microbes, such as Lactobacillus, Clostridium and Akkermansia, while it reduced pathogenic microbes, such as Enterobacter, Erysipelatoclostridium and Colidextribacter. Allicin gavage increased the abundance of intestinal short-chain fatty acids, such as acetic acid and propionic acid. Correlation analysis showed that the increased gut microbes by allicin gavage were significantly associated with health physiological parameters but negatively related to serum inflammatory factors such as interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-a), and hypersensitive C-reactive protein (hs-CRP). In addition, our study also suggests that allicin may have prebiotic effects on chronic liver injury. This study shows that allicin can regulate various clinical symptoms of T2DM and is a potential therapeutic drug for T2DM.